Curating within the Storm. Issue 2 (1st September 2022) - Bhagwati, Sandeep; Andersen, Tawny; Carrasco, Victoria; Davida, Dena; Scales, Barbara; Sheriff, Yves
Abstract : We are living through a great disturbance or, as Amitav Ghosh has called it, a "great derangement." Over decades that, in retrospect, now seem like a treacherous lull, many in the so-called Global North could maintain a belief, anchored in the everyday work of transnational institutions, that we had somehow managed to tame the four mythical riders of the apocalypse—death, pestilence, war of conquest, and famine—and that we were on track in curbing the rise of a fifth: the self-harm we as a species inflict by making our planet increasingly less habitable. The rise of self-serving, anti-globalist, anti-truth and anti-reality movements and leaders before and during the last two-and-a-half years of the COVID-19 pandemic—which is now expected to be but the first of many to come—began to erode such benevolent hopes for our future histories. The Russian invasion of Ukraine on 24 February 2022, with its barbaric strategy based on scorching the earth and systematically murdering civilians, its dire consequences for food chains worldwide, and its sidelining of efforts in the climate crisis, has only brought more gloom. The five riders are not only back—they now reinforce each other.